ANALISIS PENGARUH NET DOMESTIC ASSET, INVESTASI, DAN DANA PERBANKAN TERHADAP MONEY SUPPLY DI INDONESIA - Oktaviani, Riwindi; Budi Marwoto, Pan; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
This undergraduate thesis is a study conducted by Riwindi Oktaviani, an Accounting Program student with identity number 130140048. It is entitled in Indonesian: "Analisis Perkembangan Net Domestic Asset, Investasi, dan Dana Perbankan Terhadap Money Supply di Indonesia 2010-2016". It was supervised by Pan Budi Marwoto and Stefanus Prima Nugroho. This study was conducted from April 2018 to June 2018. The motivation to conduct this research is based on the uncertainty of net domestic asset, investment, and banking funding influence on the money supply in Indonesia. In addition, the position of the money supply is very important and must be stable so as not to cause inflation in Indonesia so that people can avoid the threat of poverty. The purpose of this study is to prove and verify the effect of net domestic asset development, investment, and banking funds on the money supply in Indonesia. The data used in this research is secondary data (in the form of time series data). Time series data in this study was used from 2010 to 2016 taken from the Central Bureau of Statistics, Engineering data processing, and analysis in this research using Multiple Linear Regression Analysis and hypothesis testers. Hypothesis testing using t-test and F-test with 5% significant level. This study also uses the coefficient of determination (R2) to determine the ability of independent variables in explaining the dependent variable. banking fund. While the remaining 0.0137 is explained by other factors outside this study.